Penggunaan Metode berbasis Kasus dalam E-learning pada Mata Kuliah Konsep Dasar IPS untuk menanamkan Nilai Sosial-budaya dan Spiritual di STAI Al-Azhar Menganti Gresik - Agustin, Nurul (Universitas Muhammadiyah Gresik, 2023)
The use of technology encourages people to change the way they interact, get to know new cultures and understand new styles of beliefs. Culture has an important role in life as habits that need to be preserved and trusted. Cultural developments have also developed in the world of entertainment. This research examines how beliefs are applied in everyday life based on the culture that develops in society. In this research, we will create learning videos and e-learning. It is necessary to naturalize the environment presented in an effort to form socio-cultural and spiritual character. The aim of this research is to find out how to develop case-based methods in e-learning, and to design learning using case-based methods in e-learning to instill socio-cultural and spiritual values ​​at STAI Al-Azhar Menganti Gresik and to find out how to increase the instillation of socio-cultural concepts and spirituality for students after learning at STAI Al-Azhar Menganti Gresik. This research uses research and development design from ADDIE with the stages of analyze, design, development, implementation and evaluation. By conducting field trials using a one-group pretest-posttest experimental design. The research results show that the Islamic academic environment and the socio-cultural environment of local life provide stimulation for student life. In this research, we review this phenomenon again in e-learning learning videos using the case method. The results show that students can explain the socio-cultural and spiritual environment by 84%. And the learning achievements in this course show that students are able to follow and complete assignments, mid-semester exams and final semester exams at 80%. Based on the hypothesis from the left side test. From the table above, the average pretest value is = 65 and the average posttest value is = 84. So the average posttest value > the average pretest value, so Ho is rejected. Because Ho experienced rejection, it can be concluded that learning outcomes without using the case method in e-learning are smaller than learning outcomes using the case method in e-learning or in other words learning outcomes increased after receiving treatment using the case method in e-learning